Cash for Honours : The Story of Maundy Gregory - Cook, Andrew (Stroud Sutton The History Press, 2008)
For the first time, this book reveals the true story of Maundy Gregory, the man responsible for 'An Insult to the Crown'. It reveals for the first time the names of the individuals who purchased titles and influence from Lloyd George.
Include Illustrations, Notes, Bibliography and Index
Keywords: Political corruption -- Great Britain